Self-lubricating composite coating for reducing the dynamic / static friction coefficient of aerodynamic rods and method for its production
Patent Information
- Application Number
- CN202611462426.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
传统的气动杆表面强化处理技术如渗碳、渗氮、碳氮共渗、电镀、激光表面强化、热喷涂等已不能满足其兼具大气/真空环境中的低摩擦与耐磨损的性能要求
[0015]所述软质润滑层的沉积条件包括:Ar气流量28 sccm,负偏压-110 V,C靶电流3.0A,氢气流量480 sccm,沉积1500~1800s。
Smart Images

Figure CN122979826A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of surface treatment technology, and in particular to a self-lubricating composite coating for reducing the dynamic / static friction coefficient of pneumatic rods and its preparation method. Background Technology
[0002] Vacuum systems are core components of critical high-altitude components of aero-engines and airborne precision equipment; their operational reliability directly determines the safety of aviation equipment. Vacuum valves, as core components for gas control and isolation in vacuum systems, undertake critical tasks such as propellant control, cabin depressurization, and system isolation. Pneumatic rods, as the core linear motion component of vacuum bellows shut-off valves, are widely used in various types of aerospace vacuum valves. The pneumatic rod is installed inside the valve cylinder and uses compressed air as a power source to drive the vacuum valve to open and close. During operation, the pneumatic rod is subjected to pressure and relative movement with the lateral valve and seals. It experiences surface wear due to friction from alternating loads in atmospheric and vacuum environments. Therefore, the pneumatic rod in vacuum valves must have low friction during the initial stage and possess a certain degree of wear resistance.
[0003] With the rapid development of vacuum machinery manufacturing and repair, issues related to the surface strengthening technology of vacuum valve components urgently need to be addressed. Traditional surface strengthening technologies for pneumatic rods, such as carburizing, nitriding, carbonitriding, electroplating, laser surface strengthening, and thermal spraying, can no longer meet their performance requirements of low friction and wear resistance in both atmospheric and vacuum environments. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a self-lubricating composite coating for reducing the dynamic / static friction coefficient of pneumatic rods and its preparation method. The self-lubricating composite coating provided by this invention can effectively reduce the friction of pneumatic rods during multiple start-up stages in atmospheric and vacuum environments, thereby improving the reliability and service life of the pneumatic rods.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a self-lubricating composite coating for reducing the dynamic / static friction coefficient of a pneumatic rod, comprising an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer sequentially stacked on the surface of the pneumatic rod; wherein the alloy bonding layer is in direct contact with the surface of the pneumatic rod. The alloy bonding layer is composed of a MoCu alloy, wherein the Cu atomic content is 15.8~18.8 at.%; The gradient transition layer is composed of Mo or Ti nitrides, with the number of N atoms gradually decreasing from 40-45 at.% to less than 5 at.% from the inside out. The high-entropy carbide layer is composed of ZrMoTiCuSiC, with a C atom content of 5~15 at.% and Zr, Mo, Ti, Cu and Si atom contents independently within 20 at.% and greater than 0. The carbide transition layer is composed of MoC or TiC, and from the inside out, the C atom content in the coating gradually increases from 5~15 at.% to more than 40 at.%; The soft lubricating layer is composed of polymer-like carbon, with an H atom content of 30~75 at.% and the balance being C.
[0006] Preferably, the thickness of the alloy bonding layer is 0.1~0.3 μm.
[0007] Preferably, the thickness of the gradient transition layer is 0.1~0.3 μm.
[0008] Preferably, the thickness of the high-entropy carbide layer is 1.5~2.0 μm.
[0009] Preferably, the thickness of the carbide transition layer is 0.1~0.3 μm.
[0010] Preferably, the thickness of the soft lubricating layer is 0.2~0.3 μm, the hardness is ≤5 GPa, the static friction coefficient in the atmosphere is <0.1, and the static friction coefficient in the vacuum is <0.1.
[0011] This invention provides a method for preparing the self-lubricating composite coating for reducing the dynamic / static friction coefficient of pneumatic rods as described above, comprising the following steps: By using magnetron sputtering, an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer are sequentially deposited on the surface of a pneumatic rod to obtain a self-lubricating composite coating that reduces the dynamic / static friction coefficient of the pneumatic rod.
[0012] Preferably, the deposition conditions for the alloy bonding layer include: Ar gas flow rate 25~40 sccm, negative bias voltage -80~-120 V, Mo target current 3.0 A, Cu target current 1.5 A, and deposition time 300~500 s; The deposition conditions of the gradient transition layer include: when the composition is MoN, the Mo target current is linearly reduced from 3A to 1A, the N2 gas flow rate is linearly reduced from 260 ccm to 0 sccm, the bias voltage is -400V, and the deposition time is 300~500s; when the composition is TiN, the Ti target current is linearly reduced from 3A to 1A, the N2 gas flow rate is linearly reduced from 260 ccm to 0 sccm, and the deposition time is 300~500s.
[0013] Preferably, the deposition conditions of the high-entropy carbide layer include: Ar gas flow rate 28 sccm, negative bias voltage -110 V, Mo target current 1.0 A, Cu target current 1.2 A, C target current 1.0 A, ZrTiSi ternary alloy target current 1.5 A, and deposition time 2~4 h. The ZrTiSi ternary alloy target contains 40-50% Zr, 30-40% Ti, and 10-30% Si by mass percentage.
[0014] Preferably, the deposition conditions of the carbide transition layer include: when the composition is MoC, the Ar gas flow rate is 28 sccm, the negative bias voltage is -110 V, the Mo target current decreases linearly from 1.0 A to 0 A, the C target current increases linearly from 1.0 A to 3.0 A, and the deposition time is 300~500 s; when the composition is TiC, the Ar gas flow rate is 28 sccm, the negative bias voltage is -110 V, the Ti target current decreases linearly from 1.0 A to 0 A, the C target current increases linearly from 1.0 A to 3.0 A, and the deposition time is 300~500 s.
[0015] The deposition conditions for the soft lubricating layer include: Ar gas flow rate 28 sccm, negative bias voltage -110 V, C target current 3.0 A, hydrogen gas flow rate 480 sccm, and deposition time 1500~1800 s.
[0016] This invention provides a self-lubricating composite coating for reducing the dynamic and static friction coefficients of pneumatic rods. During friction, hydrogen atoms in the coating are tightly bonded to carbon atoms through strong covalent bonds (referring to hydrogen and carbon atoms in the soft lubricating layer), effectively terminating dangling bonds on the carbon surface and significantly reducing the number of surface active sites, thereby reducing the adhesion between the coating and the mating material. When hydrogen atoms pair with dangling bonds on the carbon surface, the charge density shifts towards the hydrogen nucleus, bringing hydrogen protons closer to the surface. This change in charge distribution forms a bipolar structure at the sliding interface, generating a repulsive force rather than a traditional attractive force, thus significantly reducing friction. This invention integrates a self-lubricating and wear-resistant composite coating on the surface of the pneumatic rod, significantly extending its service life by 2 to 3 times. Specifically, the multilayer composite coating of the present invention forms a "hard-tough-soft" composite structure through a gradient design of "hard load-tough transition-lubrication friction reduction". The high-entropy carbide layer provides hard wear-resistant support, the gradient transition layer and the carbide transition layer inhibit crack propagation into the matrix through stress dispersion and crack deflection mechanisms, and the soft lubrication layer achieves adaptive lubrication by dynamically replenishing lubricant, maintaining a low friction state under vacuum and atmospheric conditions, and ultimately achieving a synergistic improvement in wear resistance and fatigue resistance.
[0017] The results of the embodiments show that the self-lubricating composite coating provided by the present invention can reduce the static friction coefficient of the pneumatic rod in vacuum and atmospheric atmosphere, as well as the tribological properties during the alternating process of the two environments, thus satisfying the lubrication effect and multi-environment adaptability of the pneumatic rod during the start-up process in various environments.
[0018] The design, consisting of an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer deposited sequentially on the substrate surface, provides excellent support and interfacial bonding for the self-lubricating and wear-resistant composite coating on the pneumatic rod surface. This overcomes various wear caused by alternating loads on the pneumatic valve surface, meets the requirements for mechanical properties, wear resistance, and impact resistance of the pneumatic rod surface, and effectively improves the reliability and service life of the pneumatic rod.
[0019] This invention reduces the replacement frequency of pneumatic rods by depositing a self-lubricating and wear-resistant composite coating on the surface of the pneumatic rod, saving manufacturing and replacement costs, saving a lot of manpower and resources, while ensuring the stability of the equipment system and ensuring safe production.
[0020] The self-lubricating composite coating provided by this invention reduces the dynamic / static friction coefficient of pneumatic rods, taking into account the needs of lubrication, wear resistance and adaptability to multiple environments. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the self-lubricating composite coating of the present invention; Figure 2 The results of the adhesion test between the self-lubricating composite coating of Example 1 and 15-5PH steel are shown. Figure 3 The results of the adhesion test between the self-lubricating composite coating and 15-5PH steel in Example 2 are shown. Figure 4 The results show the adhesion test between the self-lubricating composite coating of Comparative Example 1 and 15-5PH steel. Figure 5 The results show the adhesion test between the self-lubricating composite coating of Comparative Example 2 and 15-5PH steel. Figure 6 The results show the adhesion test between the self-lubricating composite coating of Comparative Example 3 and 15-5PH steel. Figure 7 The results show the adhesion test between the self-lubricating composite coating of Comparative Example 4 and 15-5PH steel. Figure 8 The results show the adhesion test between the self-lubricating composite coating of Comparative Example 5 and 15-5PH steel. Figure 9 The friction coefficient curve of the self-lubricating composite coating in the atmosphere is shown in Example 2. Figure 10The friction coefficient curve of the self-lubricating composite coating in vacuum is shown in Example 2. Figure 11 The friction coefficient curve of the composite coating in the atmosphere is shown in Comparative Example 2. Figure 12 The friction coefficient curve of the self-lubricating composite coating of Example 2 when it is converted from an atmospheric environment to a vacuum environment; Figure 13 The friction coefficient curve of the self-lubricating composite coating of Example 2 in a vacuum environment is shown. Detailed Implementation
[0022] like Figure 1 As shown, the present invention provides a self-lubricating composite coating for reducing the dynamic / static friction coefficient of a pneumatic rod, comprising an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer sequentially stacked on the surface of the pneumatic rod; the alloy bonding layer is in direct contact with the surface of the pneumatic rod. The alloy bonding layer is composed of a MoCu alloy, wherein the Cu atomic content is 15.8~18.8 at.%; The gradient transition layer is composed of Mo or Ti nitrides, with the number of N atoms gradually decreasing from 40-45 at.% to less than 5 at.% from the inside out. The high-entropy carbide layer is composed of ZrMoTiCuSiC, with a C atom content of 5~15 at.% and Zr, Mo, Ti, Cu and Si atom contents independently within 20 at.% and greater than 0. The carbide transition layer is composed of MoC or TiC, and from the inside out, the C atom content in the coating gradually increases from 5~15 at.% to more than 40 at.%; The soft lubricating layer is composed of polymer-like carbon, with an H atom content of 30~75 at.% and the balance being C.
[0023] In this invention, the pneumatic rod is preferably made of precipitation-hardening stainless steel, specifically 15-5PH, 17-4PH, or austenitic stainless steel. In this invention, the pneumatic rod is preferably a pneumatic rod that has undergone aging treatment.
[0024] The self-lubricating composite coating provided by this invention includes an alloy bonding layer attached to the surface of a pneumatic rod. In this invention, the alloy bonding layer is composed of a MoCu alloy, wherein the Cu atomic content is 15.8~18.8 at.%; in specific embodiments, the Cu atomic content in the alloy bonding layer can be 15.8, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, or 18.8 at.%. In this invention, the thickness of the alloy bonding layer is preferably 0.1~0.3 μm, and in specific embodiments, it can be 0.1, 0.15, 0.2, 0.25, or 0.3 μm. In this invention, the hardness of the alloy bonding layer is preferably >8 GPa. In this invention, the function of the alloy bonding layer is to improve the bonding strength between the composite coating and the pneumatic rod. In this invention, the alloy bonding layer preferably contacts the substrate through chemical bonding. Specifically, the substrate is activated by vacuum plasma, and Fe, Cr, and other atoms in the substrate and Mo and Cu in the coating diffuse and replace each other to form a new solid solution. Mo atoms partially replace Fe atoms to form a solid solution, enhancing the material's strength; Cr and Mo form an infinite substitution solid solution, improving the material's wear resistance.
[0025] The self-lubricating composite coating provided by this invention includes a gradient transition layer attached to the surface of an alloy bonding layer. In this invention, the gradient transition layer is composed of Mo or Ti nitrides (i.e., MoN or TiN), with the N atom content gradually decreasing from 40-45 at.% to less than 5 at.% from the inside out. In this invention, the thickness of the gradient transition layer is preferably 0.1-0.3 μm, and in specific embodiments, it can be 0.1, 0.15, 0.2, 0.25, or 0.3 μm. In this invention, the hardness of the gradient transition layer is preferably >12 GPa. In this invention, the function of the gradient transition layer is to achieve a transition in mechanical properties between the alloy bonding layer and the high-entropy carbide layer through a change in compositional gradient.
[0026] The self-lubricating composite coating provided by this invention includes a high-entropy carbide layer attached to the surface of a gradient transition layer. In this invention, the high-entropy carbide layer is composed of ZrMoTiCuSiC, with a C atom content of 5-15 at.%, and the atom contents of Zr, Mo, Ti, Cu, and Si are independently within 20 at.% and greater than 0. In specific embodiments, the C atom content in the high-entropy carbide layer can be 5, 7, 8, 10, 12, 13, 14, or 15 at.%; the atom contents of Zr, Mo, Ti, Cu, and Si can be independently 5-20 at.%, or 10-18 at.%. In this invention, the thickness of the high-entropy carbide layer is preferably 1.5-2.0 μm, and in specific embodiments, it can be 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 μm. The hardness of the high-entropy carbide layer is preferably >16 GPa. In this invention, the high-entropy carbide layer is used to provide high hardness and anti-wear properties.
[0027] The self-lubricating composite coating provided by this invention includes a carbide transition layer attached to the surface of a high-entropy carbide layer. In this invention, the carbide transition layer is composed of MoC or TiC, and the C atom content in the coating gradually increases from 5-15 at.% to over 40 at.% from the inside out. In specific embodiments, the innermost C atom content of the carbide transition layer can be 5, 7, 8, 10, 12, 13, 14, or 15 at.%, and the outermost C atom content can be 40-45 at.%. In this invention, the thickness of the carbide transition layer is preferably 0.1-0.3 μm, and in specific embodiments, it can be 0.1, 0.15, 0.2, 0.25, or 0.3 μm. The hardness of the carbide transition layer is preferably 8-16 GPa. In this invention, the function of the carbide transition layer is to adjust the compositional gradient between the high-entropy carbide layer and the soft lubricating layer, and simultaneously serve as a carrier for the lubricating phase.
[0028] The self-lubricating composite coating provided by this invention includes a soft lubricating layer attached to the surface of a carbide transition layer. In this invention, the soft lubricating layer is composed of polymer-like carbon (PLC), with an H atom content of 30-75 at.%, and the balance being C. In specific embodiments, the H atom content in the soft lubricating layer can be 30, 35, 40, 45, 50, 55, 60, 65, 70, or 75 at.%. In this invention, the thickness of the soft lubricating layer is preferably 0.2-0.3 μm, the hardness is preferably ≤5 GPa, the static friction coefficient in atmosphere is preferably <0.1, and the static friction coefficient in vacuum is preferably <0.1. In this invention, the soft lubricating layer is a low-shear-strength carbon-based material, providing initial running-in action and forming a lubricating film at the friction interface.
[0029] In this invention, the thickness of the self-lubricating composite coating is preferably 2.0~3.2 μm. In specific embodiments, it can be 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, or 3.2 μm. A thinner coating thickness ensures that the pneumatic rod substrate has improved tribological properties and is easier to process without affecting its original dimensions.
[0030] This invention provides a method for preparing the self-lubricating composite coating for reducing the dynamic / static friction coefficient of pneumatic rods as described above, comprising the following steps: By using magnetron sputtering, an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer are sequentially deposited on the surface of a pneumatic rod to obtain a self-lubricating composite coating that reduces the dynamic / static friction coefficient of the pneumatic rod.
[0031] Before depositing the alloy bonding layer, the pneumatic rod is preferably activated by plasma bombardment. In this invention, the plasma bombardment activation preferably includes: placing the cleaned pneumatic rod to be deposited in the vacuum chamber of a vacuum vapor deposition system, and pre-evacuating the vacuum to 3 × 10⁻⁶. -3 Below Pa, argon and / or hydrogen are introduced to achieve a pressure of 0.5~2.0 Pa in the vacuum chamber. A bias voltage of -600~-1000 V is applied to the pneumatic rod to generate plasma glow on its surface for 30 min of surface activation treatment. This invention employs plasma bombardment activation to deeply clean and activate the substrate surface through a synergistic effect of physical and chemical processes. The sputtering effect is used to remove adsorbed hydrocarbons, oxide layers, and particulate contaminants from the surface; plasma bombardment disrupts the original chemical bonds on the substrate surface, generating free radicals and "anchoring points" for deposited particles, thus enhancing the film-substrate bonding strength.
[0032] In this invention, an alloy bonding layer is first deposited.
[0033] In this invention, the preferred deposition conditions for the alloy bonding layer include: Ar gas flow rate of 25~40 sccm, negative bias voltage of -80~-120 V, Mo target current of 3.0 A, Cu target current of 1.5 A, and deposition time of 300~500 s. In specific embodiments, the Ar gas flow rate can be 25, 30, 35 or 40 sccm, and the negative bias voltage can be -80, -90, -100, -110 or -120 V.
[0034] After forming the alloy bonding layer, the present invention deposits a gradient transition layer on the surface of the alloy bonding layer.
[0035] In this invention, the deposition conditions of the gradient transition layer preferably include: when the composition is MoN, controlling the Mo target current to decrease linearly from 3A to 1A, the N2 gas flow rate to decrease linearly from 260 ccm to 0 sccm, the bias voltage to -400V, and the deposition time to 300~500s; when the composition is TiN, controlling the Ti target current to decrease linearly from 3A to 1A, the N2 gas flow rate to decrease linearly from 260 ccm to 0 sccm, and the deposition time to 300~500s.
[0036] After forming the gradient transition layer, the present invention deposits a high-entropy carbide layer on the surface of the gradient transition layer.
[0037] In this invention, the preferred deposition conditions for the high-entropy carbide layer include: Ar gas flow rate 28 sccm, negative bias voltage -110 V, Mo target current 1.0 A, Cu target current 1.2 A, C target current 1.0 A, ZrTiSi ternary alloy target current 1.5 A, and deposition time 2-4 h; by mass percentage, the Zr content in the ZrTiSi ternary alloy target is preferably 40-50%, the Ti content is preferably 30-40%, and the Si content is preferably 10-30%.
[0038] After forming a high-entropy carbide layer, the present invention deposits a carbide transition layer on the surface of the high-entropy carbide layer.
[0039] In this invention, when the carbide transition layer is composed of MoC, the preferred deposition conditions for the carbide transition layer include: Ar gas flow rate of 28 sccm, negative bias voltage of -110 V, Mo target current linearly decreasing from 1.0 A to 0 A, C target current linearly increasing from 1.0 A to 3.0 A, and deposition time of 300-500 s. When the carbide transition layer is composed of TiC, the preferred deposition conditions for the carbide transition layer include: Ar gas flow rate of 28 sccm, negative bias voltage of -110 V, Ti target current linearly decreasing from 1.0 A to 0 A, C target current linearly increasing from 1.0 A to 3.0 A, and deposition time of 300-500 s.
[0040] After forming the carbide transition layer, the present invention deposits a soft lubricating layer on the surface of the carbide transition layer.
[0041] In this invention, the preferred deposition conditions for the soft lubricating layer include: Ar gas flow rate of 28 sccm, negative bias voltage of -110 V, C target current of 3.0 A, hydrogen gas flow rate of 480 sccm, and deposition time of 1500~1800 s.
[0042] Pneumatic rods, which also serve a gas sealing function, require high precision. Processes such as carburizing, nitriding, carbonitriding, and laser surface strengthening are prone to heat treatment deformation and thermal stress cracking, resulting in high scrap rates. This invention employs physical and chemical vapor deposition (PVD) technology. The temperature during the deposition of the self-lubricating composite coating is lower than that of nitriding and laser strengthening, thus avoiding product scrapping problems caused by high temperatures.
[0043] The following detailed description, in conjunction with embodiments, of the self-lubricating composite coating for reducing the dynamic / static friction coefficient of pneumatic rods and its preparation method provided by the present invention, should not be construed as limiting the scope of protection of the present invention.
[0044] Example 1 In this embodiment, the substrate is a 15-5PH pneumatic rod with a hardness ≥55HRC after aging treatment. The total thickness of the self-lubricating composite coating on the surface of the pneumatic rod to reduce the dynamic / static friction coefficient is controlled at 2.5 μm. The composition is as follows: from the inside to the outside, the 15-5PH pneumatic rod consists of a MoCu alloy bonding layer with a thickness of 0.1 μm; a MoN gradient transition layer with a thickness of 0.1 μm; a ZrMoTiCuSiC high-entropy carbide coating with a thickness of 2.0 μm; a MoC carbide transition layer with a thickness of 0.1 μm; and a PLC soft lubricating coating with a thickness of 0.2 μm.
[0045] The method for preparing a self-lubricating composite coating is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon gas is introduced to make the pressure in the vacuum chamber 1.5 Pa. A bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo, Cu, C and ZrTiSi ternary alloy targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 300 s. Step 3) Deposit MoN gradient transition layer A MoN gradient transition layer was prepared on the alloy bonding layer. The Mo target current was linearly reduced from 3A to 1.0A, the N2 gas flow rate was linearly reduced from 260 ccm to 0 sccm, the bias voltage was -400V, and the deposition time was 300s. Step 4) Deposition of ZrMoTiCuSiC high-entropy carbide layer A high-entropy carbide layer was prepared on the gradient transition layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current of 1.0 A, a Cu target current of 1.2 A, a C target current of 1.0 A, and a ZrTiSi ternary alloy target current of 1.5 A. The deposition time was 2.5 h. Step 5) Deposit MoC carbide transition layer A carbide transition layer was prepared on a high-entropy carbide layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current that decreased linearly from 1.0 A to 0 A, and a C target current that increased linearly from 1.0 A to 3.0 A, and a deposition time of 300 s.
[0046] Step 5) Deposit a soft lubricating layer for the PLC A PLC soft lubricating layer was prepared on the carbide transition layer. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the C target current was 3.0 A, the hydrogen gas flow rate was 480 sccm, and the deposition time was 1500 s.
[0047] Example 2 In this embodiment, the substrate is a 15-5PH pneumatic rod with a hardness ≥55HRC after aging treatment. The total thickness of the self-lubricating composite coating on the surface of the pneumatic rod to reduce the dynamic / static friction coefficient is controlled at 3.2 μm. The composition is as follows: from the inside to the outside, the 15-5PH pneumatic rod consists of a MoCu alloy bonding layer with a thickness of 0.3 μm; a TiN gradient transition layer with a thickness of 0.3 μm; a ZrMoTiCuSiC high-entropy carbide coating with a thickness of 2.0 μm; a MoC carbide transition layer with a thickness of 0.3 μm; and a PLC soft lubricating coating with a thickness of 0.3 μm.
[0048] The preparation method of the self-lubricating composite coating is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon gas is introduced to make the pressure in the vacuum chamber 1.5 Pa. A bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo, Cu, C and ZrTiSi ternary alloy targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 500 s. Step 3) Deposit TiN gradient transition layer Ti nitride films were prepared on the alloy bonding layer. The Ti target current was linearly reduced from 3A to 1.0A, the N2 gas flow rate was linearly reduced from 260 ccm to 0 sccm, the bias voltage was -400V, and the deposition time was 500s. Step 4) Deposition of ZrMoTiCuSiC high-entropy carbide layer A high-entropy carbide layer was prepared on the gradient transition layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current of 1.0 A, a Cu target current of 1.2 A, a C target current of 1.0 A, and a ZrTiSi ternary alloy target current of 1.5 A. The deposition time was 2.5 h. Step 5) Deposit MoC carbide transition layer A carbide transition layer was prepared on a high-entropy carbide layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current that decreased linearly from 1.0 A to 0 A, and a C target current that increased linearly from 1.0 A to 3.0 A, and a deposition time of 500 s.
[0049] Step 6) Deposit a soft lubricating layer A soft lubricating layer was prepared on the carbide transition layer with an Ar gas flow rate of 28 sccm, a negative bias voltage of -110 V, a C target current of 3.0 A, a hydrogen gas flow rate of 480 sccm, and a deposition time of 1800 s.
[0050] Comparative Example 1 In this comparative example, the substrate is a 15-5PH pneumatic rod with a hardness ≥55HRC after aging treatment. The total thickness of the self-lubricating composite coating on the pneumatic rod surface, which reduces the dynamic / static friction coefficient of the pneumatic rod, is controlled at 0.6 μm. The composition is as follows: from the inside to the outside of the 15-5PH pneumatic rod, it consists of a MoCu alloy with a thickness of 0.3 μm; and a PLC soft lubricating coating with a thickness of 0.3 μm.
[0051] The method for preparing the self-lubricating composite coating on the surface of the pneumatic rod to reduce the dynamic / static friction coefficient of the pneumatic rod is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon and / or hydrogen are introduced to make the pressure in the vacuum chamber 0.5~2.0 Pa, and a bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo and Cu targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 500 s. Step 3) Deposit a soft lubricating layer A soft lubricating layer was prepared on the carbide transition layer with an Ar gas flow rate of 28 sccm, a negative bias voltage of -110 V, a C target current of 3.0 A, a hydrogen gas flow rate of 480 sccm, and a deposition time of 1800 s.
[0052] Comparative Example 2 The difference from Example 1 is that the carbide transition layer and the soft lubricating layer are omitted.
[0053] The method for preparing the self-lubricating composite coating on the surface of the pneumatic rod to reduce the dynamic / static friction coefficient of the pneumatic rod is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon and / or hydrogen are introduced to make the pressure in the vacuum chamber 1.5 Pa, and a bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo, Cu, C and ZrTiSi ternary alloy targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 300 s. Step 3) Deposit MoN gradient transition layer Mo nitride films were prepared on the alloy bonding layer. The Mo target current was linearly reduced from 3A to 1.0A, the N2 gas flow rate was linearly reduced from 260 ccm to 0 sccm, the bias voltage was -400V, and the deposition time was 300s. Step 4) Deposition of ZrMoTiCuSiC high-entropy carbide layer A high-entropy carbide layer was prepared on the gradient transition layer with an Ar gas flow rate of 28 sccm, a negative bias voltage of -110 V, a Mo target current of 1.0 A, a Cu target current of 1.2 A, a C target current of 1.0 A, and a ZrTiSi ternary alloy target current of 1.5 A. The deposition time was 2.5 h.
[0054] Comparative Example 3 The only difference from Example 1 is that the high-entropy carbide layer is omitted.
[0055] The method for preparing a self-lubricating composite coating is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon gas is introduced to make the pressure in the vacuum chamber 1.5 Pa. A bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo, Cu, C and ZrTiSi ternary alloy targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 300 s. Step 3) Deposit MoN gradient transition layer A MoN gradient transition layer was prepared on the alloy bonding layer. The Mo target current was linearly reduced from 3A to 1.0A, the N2 gas flow rate was linearly reduced from 260 ccm to 0 sccm, the bias voltage was -400V, and the deposition time was 300s. Step 4) Deposition of ZrMoTiCuSiC high-entropy carbide layer A high-entropy carbide layer was prepared on the gradient transition layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current of 1.0 A, a Cu target current of 1.2 A, a C target current of 1.0 A, and a ZrTiSi ternary alloy target current of 1.5 A. The deposition time was 2.5 h. Step 5) Deposit a soft lubricating layer for the PLC A PLC soft lubricating layer was prepared on the carbide transition layer. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the C target current was 3.0 A, the hydrogen gas flow rate was 480 sccm, and the deposition time was 1500 s.
[0056] Comparative Example 4 The only difference from Example 1 is that the gradient transition layer is omitted.
[0057] The method for preparing a self-lubricating composite coating is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon gas is introduced to make the pressure in the vacuum chamber 1.5 Pa. A bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo, Cu, C and ZrTiSi ternary alloy targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 300 s. Step 3) Deposition of ZrMoTiCuSiC high-entropy carbide layer A high-entropy carbide layer was prepared on the gradient transition layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current of 1.0 A, a Cu target current of 1.2 A, a C target current of 1.0 A, and a ZrTiSi ternary alloy target current of 1.5 A. The deposition time was 2.5 h. Step 4) Deposit MoC carbide transition layer A carbide transition layer was prepared on a high-entropy carbide layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current that decreased linearly from 1.0 A to 0 A, and a C target current that increased linearly from 1.0 A to 3.0 A, and a deposition time of 300 s.
[0058] Step 5) Deposit a soft lubricating layer for the PLC A PLC soft lubricating layer was prepared on the carbide transition layer. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the C target current was 3.0 A, the hydrogen gas flow rate was 480 sccm, and the deposition time was 1500 s.
[0059] Comparative Example 5 The difference from Example 1 is that the carbide transition layer is omitted.
[0060] The method for preparing a self-lubricating composite coating is as follows: Step 1) Plasma bombardment activation The cleaned pneumatic rod to be plated is placed in the vacuum chamber of the vapor deposition system, and the vacuum is pre-evacuated to 3 × 10⁻⁶. -3 Below Pa, argon gas is introduced to make the pressure in the vacuum chamber 1.5 Pa. A bias voltage of -800 V is applied to the pneumatic rod to generate plasma glow on the surface of the pneumatic rod for surface activation treatment for 30 min. Step 2) Deposit MoCu alloy bonding layer An alloy bonding layer was prepared on the surface of the pneumatic rod. High-purity Mo, Cu, C and ZrTiSi ternary alloy targets were installed in a multi-target unbalanced magnetron sputtering system. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the Mo target current was 3.0 A, the Cu target current was 1.5 A, and the deposition time was 300 s. Step 3) Deposit MoN gradient transition layer A MoN gradient transition layer was prepared on the alloy bonding layer. The Mo target current was linearly reduced from 3A to 1.0A, the N2 gas flow rate was linearly reduced from 260 ccm to 0 sccm, the bias voltage was -400V, and the deposition time was 300s. Step 4) Deposition of ZrMoTiCuSiC high-entropy carbide layer A high-entropy carbide layer was prepared on the gradient transition layer with an Ar gas flow rate of 28 sccm, a negative bias of -110 V, a Mo target current of 1.0 A, a Cu target current of 1.2 A, a C target current of 1.0 A, and a ZrTiSi ternary alloy target current of 1.5 A. The deposition time was 2.5 h. Step 5) Deposit a soft lubricating layer for the PLC A PLC soft lubricating layer was prepared on the carbide transition layer. The Ar gas flow rate was 28 sccm, the negative bias voltage was -110 V, the C target current was 3.0 A, the hydrogen gas flow rate was 480 sccm, and the deposition time was 1500 s.
[0061] Performance testing: The adhesion strength of the coatings in the examples and comparative examples was tested according to JB / T 8554-1997. The test results are shown below. Figures 2-8 The specific data is shown in Table 1.
[0062] Table 1. Bonding strength test results of the examples and comparative examples.
[0063] As can be seen from the data in Table 1, the bonding strength between the composite coatings of Comparative Examples 4 and 5 and the substrate is significantly lower than that of Example 1. This indicates that the carbide transition layer and the gradient transition layer can reduce the mismatch between the microstructures of the layers through the change of compositional gradient, thereby improving the bonding strength.
[0064] The tribological properties of the coating were evaluated using a ball-disc tribological tester in reciprocating mode, with a load of 5 N, an amplitude of 2.5 mm, a frequency of 5 Hz, and a Φ6 mm GCr15 ball as the mating element. Test results are shown below. Figures 9-13 And Table 1. Among them, Figure 9 The friction coefficient curve of the self-lubricating composite coating in Example 2 is shown in the atmosphere, with an average friction coefficient of 0.05. Figure 10 The friction coefficient curve of the self-lubricating composite coating in Example 2 is shown in a vacuum, with an average friction coefficient of 0.03. Figure 11 The curve of the friction coefficient of the composite coating in the atmosphere is shown in Comparative Example 2, with an average friction coefficient of 0.45. Figure 12 The friction coefficient curve of the self-lubricating composite coating in Example 2 is shown when it is converted from an atmospheric environment to a vacuum environment. The average friction coefficient is 0.05 in the atmosphere and 0.03 when converted to a vacuum environment. The environmental conversion has little effect on the friction coefficient.
[0065] Figure 13 The friction coefficient curve of the self-lubricating composite coating in Example 2 is shown when it is converted from a vacuum environment to an atmospheric environment. The average friction coefficient is 0.03 in a vacuum, and 0.07 when it is converted to an atmospheric environment. The environmental conversion has little effect on the friction coefficient.
[0066] Table 2. Dynamic / static friction coefficients of self-lubricating composite coatings in Examples 1-2 and Comparative Examples 1-2
[0067] As shown in Table 2, the self-lubricating composite coating provided by this invention meets both the requirements of low friction and wear resistance in atmospheric / vacuum environments. Comparative Example 1, which omits the gradient transition layer, high-entropy carbide layer, and carbide transition layer, exhibits increased atmospheric and vacuum wear rates, as well as increased vacuum static / dynamic friction coefficients, leading to insufficient lifespan of the pneumatic rod in both atmospheric and vacuum environments. Comparative Example 2, which omits the carbide transition layer and soft lubricating layer, also has high atmospheric static / dynamic friction coefficients, atmospheric wear rates, vacuum static / dynamic friction coefficients, and vacuum wear rates. The increased friction coefficient is detrimental to repeated starts of the pneumatic rod in both atmospheric and vacuum environments, and the increased wear rate results in insufficient lifespan of the pneumatic rod in both environments.
[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A self-lubricating composite coating for reducing the dynamic / static friction coefficient of a pneumatic rod, characterized in that, It includes an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer that are sequentially stacked on the surface of the pneumatic rod; the alloy bonding layer is in direct contact with the surface of the pneumatic rod. The alloy bonding layer is composed of a MoCu alloy, wherein the Cu atomic content is 15.8~18.8 at.%; The gradient transition layer is composed of Mo or Ti nitrides, with the number of N atoms gradually decreasing from 40-45 at.% to less than 5 at.% from the inside out. The high-entropy carbide layer is composed of ZrMoTiCuSiC, with a C atom content of 5~15 at.% and Zr, Mo, Ti, Cu and Si atom contents independently within 20 at.% and greater than 0. The carbide transition layer is composed of MoC or TiC, and from the inside out, the C atom content in the coating gradually increases from 5~15 at.% to more than 40 at.%; The soft lubricating layer is composed of polymer-like carbon, with an H atom content of 30~75 at.% and the balance being C.
2. The self-lubricating composite coating according to claim 1, characterized in that, The thickness of the alloy bonding layer is 0.1~0.3 μm.
3. The self-lubricating composite coating according to claim 1, characterized in that, The thickness of the gradient transition layer is 0.1~0.3 μm.
4. The self-lubricating composite coating according to claim 1, characterized in that, The thickness of the high-entropy carbide layer is 1.5~2.0 μm.
5. The self-lubricating composite coating according to claim 1, characterized in that, The thickness of the carbide transition layer is 0.1~0.3 μm.
6. The self-lubricating composite coating according to claim 1, characterized in that, The thickness of the soft lubricating layer is 0.2~0.3 μm, the hardness is ≤5 GPa, the static friction coefficient in the atmosphere is <0.1, and the static friction coefficient in the vacuum is <0.
1.
7. The method for preparing the self-lubricating composite coating for reducing the dynamic / static friction coefficient of a pneumatic rod as described in any one of claims 1 to 6, characterized in that, Includes the following steps: By using magnetron sputtering, an alloy bonding layer, a gradient transition layer, a high-entropy carbide layer, a carbide transition layer, and a soft lubricating layer are sequentially deposited on the surface of a pneumatic rod to obtain a self-lubricating composite coating that reduces the dynamic / static friction coefficient of the pneumatic rod.
8. The preparation method according to claim 7, characterized in that, The deposition conditions for the alloy bonding layer include: Ar gas flow rate 25~40 sccm, negative bias voltage -80~-120 V, Mo target current 3.0 A, Cu target current 1.5 A, and deposition time 300~500 s; The deposition conditions of the gradient transition layer include: when the composition is MoN, the Mo target current is linearly reduced from 3A to 1A, the N2 gas flow rate is linearly reduced from 260 ccm to 0 sccm, the bias voltage is -400V, and the deposition time is 300~500s; when the composition is TiN, the Ti target current is linearly reduced from 3A to 1A, the N2 gas flow rate is linearly reduced from 260 ccm to 0 sccm, and the deposition time is 300~500s.
9. The preparation method according to claim 7, characterized in that, The deposition conditions for the high-entropy carbide layer include: Ar gas flow rate 28 sccm, negative bias voltage -110 V, Mo target current 1.0 A, Cu target current 1.2 A, C target current 1.0 A, ZrTiSi ternary alloy target current 1.5 A, and deposition time 2~4 h. The ZrTiSi ternary alloy target contains 40-50% Zr, 30-40% Ti, and 10-30% Si by mass percentage.
10. The preparation method according to claim 7, characterized in that, The deposition conditions for the carbide transition layer include: when the composition is MoC, the Ar gas flow rate is 28 sccm, the negative bias voltage is -110 V, the Mo target current decreases linearly from 1.0 A to 0 A, the C target current increases linearly from 1.0 A to 3.0 A, and the deposition time is 300~500 s; when the composition is TiC, the Ar gas flow rate is 28 sccm, the negative bias voltage is -110 V, the Ti target current decreases linearly from 1.0 A to 0 A, the C target current increases linearly from 1.0 A to 3.0 A, and the deposition time is 300~500 s. The deposition conditions for the soft lubricating layer include: Ar gas flow rate 28 sccm, negative bias voltage -110 V, C target current 3.0 A, hydrogen gas flow rate 480 sccm, and deposition time 1500~1800 s.